Correlation between lifestyle and social factors in functional dyspepsia among college freshmen. Issue 8 (August 2020) - Huang, Zhen-peng; Wang, Ke; Duan, Yu-hang; Yang, Guang
Objective: We aimed to examine the relationship between the prevalence of functional dyspepsia (FD) and lifestyle habits, to identify social factors that may contribute to psychosocial disorders. Methods: We enrolled 759 university freshmen in this study, who were categorized into the FD group and healthy group. All participants completed the validated Self-Rating Depression Scale and Self-Rating Anxiety Scale questionnaires, to assess lifestyle and social factors among participants. Results: The proportion of participants with FD was 16.86%, and 67.97% were women. Diet irregularities and sleep impairment may have an effect on FD. Tea consumption may play a role in preventing FD. Participants with FD were more likely to have mood disorders than healthy participants. Most participants with FD who had mood disorders experienced mild anxiety or depression. Participants' main sources of stress arose from daily life, development, social life, life events, and participants' daily schedule. Conclusion: Sex and lifestyle habits, including sleeping patterns and dietary habits, can have an impact on FD. Social stress and mood disorders also have an effect on FD. FD may be prevented by adjusting lifestyle habits and psychological counseling.